Simulation of Thermal Decomposition of Calcium Oxide in a Backward Step Tubular Reactor Containing a Cooling Jacket to Enhance the Heat Transfer and the Rotation Rate. (19th October 2022) - Alshehri, Nawal A.; Memon, Abid A.; Memon, M. Asif; Bhayo, Bilawal A.; Bhatti, Kaleemullah; Hejazi, Hala A.; Jacob, Kavikumar; Seidu, Jamel
Abstract : The chemical reactions widely operate in industries to enhance the heat transfer rate among the chosen domain. In the current article, we are going to observe an exothermic reaction of calcium oxide and water in a backward step tubular reactor with a cooled surrounded surface. The tubular reactor will be considered axisymmetric with an aspect ratio of 0.5, 0.6, and 0.7 from half radius to the length of the reactor. The governing partial differential equations of mass, momentum, and energy and diffusion equations are solved using the commercial package of finite element method of COMSOL Multiphysics 5.6. A parametric study is done by using the Reynolds number in the range and activation energy E in a range from 71, 000 J/mol to 75, 000 J/mol. The initial concentration of calcium oxide is tested from 1% to 3%. The computational results will be displayed for the upstream and downstream of the channel. It was concluded that the temperature difference is increasing linearly against the concentration of calcium hydroxide upstream and nonfunctional downstream. The average Sherwood and Nusselt numbers give a positive response with increasing the aspect ratio as well as the Reynolds number. The rotation rate at the middle of the downstream was also concluded using the Reynolds number and aspect ratio.